"Not Our Revolution": A Thematic Review of Fourth Industrial Revolution Criticism. Issue 3 (3rd July 2022) - Bowie, Anneli
Abstract: This article offers a thematic review of criticism directed at high-level public discourse surrounding the South African Fourth Industrial Revolution (4IR) agenda. While the South African adoption of the World Economic Forum's 4IR strategy for economic growth and skills development has been met with widespread enthusiasm, it has also attracted considerable criticism. This article thus seeks to offer insight into the debate surrounding the legitimacy and contextual propriety of the South African 4IR agenda. Insofar as the local criticism directed at the 4IR agenda reflects international criticism of the concept, the first part of this article draws on global critiques to explore objections raised against the 4IR's constitutive legitimacy. The second part of the article identifies critical themes surrounding more locally specific rejections of the 4IR agenda, such as it being an imported and contextually inappropriate framework for addressing local problems. Finally, I analyse an editorial cartoon that captures the various grounds on which the South African 4IR agenda is commonly critiqued. While this article provides insight into a particular public policy controversy, it also elucidates some general oppositional values as expressed by critics in their assessment of development rhetoric.